Preparing a homily as an important element of pastoral care - Henryk Sławiński (Polonia Sacra)
The homily, which the Second Vatican Council assigned a special role among various forms of preaching the Word of God, is an important task for those, who are entrusted with pastoral care. The faithful eagerly listen to homilies, but at the same time, they often complain that their level is too low and expect homilies on the good level. Yet, the solution to the problem lies in good preparation of the homily. Also, preachers must be convinced that the time allocated for this is one of their most important pastoral duties. We have evidence of how the last popes, Benedict XVI and Francis, prepared their homilies. Working on a sermon is a creative process that goes through the following phases: research and collection of materials, incubation, illumination, and verification. The fruit of reflection and prayer is a homily characterized by Christocentrism, a positive message from which a moral call arises; it contains the teaching of the Church, actualizes the word of God, introduces the celebrated liturgy, and is single-thematic. Hence, in the pastors’ belief in the important role of the sermon and its reliable preparation, there is an opportunity to improve the quality of the homily.